PETROGENESIS OF VOLCANIC CONES INTRA TONDANO CALDERA, NORTH SULAWESI - Ambarwati Puspanegara, Fadhilah
Tondano Caldera is the result of an explosive eruption that was formed about 1.25 - 2 million years ago in North Sulawesi. After that, volcanic activity was still ongoing, marked by the formation of volcanic cones in the Tondano Caldera, including Lokon Complex and Tampusu Complex. Previous research at Tampusu Complex only discussed the geothermal system in the surrounding area and for Lokon Complex it was necessary to update data because from 1829 to 2015 there had been 37 eruptions. This study aims to map the distribution of volcanic products, the history of the formation and evolution of magma that occurs, and to determine the tectonic setting, based on petrogenesis studies. Based on the volcanostratigraphic analysis, the study area was formed during 14 phases of formation of khuluk and gumuk consisting of 10 khuluks and 6 volcanic gumuks. The evolution of magma in the study area shows a repetition of magma differentiation processes, primitive magma injection and magma assimilation which is reflected in fluctuations in anorthite content and rock texture. Based on plagioclase microtexture analysis, the processes that occur include decompression due to primitive magma, crystal fractionation, self mixing due to convection, heating due to primitive magma mixing, cooling due to eruption, and decompression during eruption. Analysis of spider diagrams, bivariate and ternary diagrams between geochemical content, and comparisons between trace elements shows that Lokon Complex and Tampusu Complex are tectonically included in the active continental margin with medium K calc alkaline magma series.